Peran Kepramukaan Sebagai Sarana Pembelajaran Karakter - Israyanti Israyanti; Muniati Muniati; Fransiska Liliana; Agnes Novita Dua Bare; Veronika Dua Riong; Ardiansah Andika Fajar (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
Scouting is a non-formal educational movement that focuses on the formation of character, skills, and youth leadership. Through scouting activities, youth can develop values ​​such as discipline, cooperation, and social awareness. Scouting programs include outdoor activities, skill development, and community service. As a result, scouting contributes to the formation of young leaders who are characterful, independent, and care about the community. Through literature studies and descriptive analysis, this article examines how scouting activities, such as camping, exploration, and survival skills, contribute to the development of noble values, independence, discipline, and leadership. The results of the study indicate that scouting provides contextual and applicable learning experiences, strengthening the positive character of students. The implication of this study is the importance of integrating scouting values ​​in formal and non-formal education systems to create a young generation with strong character and competitiveness.